Lactic Acidosis in the Presence of Glucose Diminishes Warburg Effect in Lung Adenocarcinoma Cells - Prado-Garcia, Heriberto; Campa-Higareda, Andrea; Romero-Garcia, Susana (Frontiers in Oncology, 2020)
Lactic acidosis (3 to 40 mM, pH < 6.9) is a condition found in solid tumors because tumor cells have a high rate of glucose consumption and lactate production even in the presence of oxygen; nevertheless, the microenvironment might still provide a sufficient glucose supply. Lactic acidosis has been proposed to shift metabolism from aerobic glycolysis towards oxidative phosphorylation (OXPHOS). We tested if lung tumor cells cultured under lactic acidosis shift their metabolism from glycolysis to OXPHOS by consuming extracellular lactate, increasing growth rate. We analyzed lung adenocarcinoma (A-549, A-427) cell lines and non-transformed fibroblast cells (MRC-5), which were cultured using RPMI-1640 medium initially containing lactate (2 mM) and glucose (10 mM), at pH 7.2 or 6.2 and oxygen tension 21% O2 (normoxia) or 2% O2 (hypoxia). We obtained growth curves, as well as glucose consumption and lactate production rates (measured during exponential growth) for each cell line. HIF-1, CS (citrate synthase) and AMPK transcript levels were analyzed using RT-qPCR. By flow cytometry, we determined: a) expression of glucose transporters (GLUT)1 and 4; b) lactate transporters (MCT)1 and 4; c) cell cycle profile, and d) protein levels of HIF-1, total and phosphorylated AMPK (pAMPK). Mitochondrial functionality was evaluated by measuring O2 consumption in tumor cells using polarography and a Clark-type electrode. Tumor and non-transformed cells used both aerobic glycolysis and OXPHOS for obtaining energy. As of 48h of culture, lactate levels ranged from (4.5-14 mM), thus forming a lactic environment. Lactic acidosis diminished GLUT1/GLUT4 expression and glucose consumption in A-549, but not in A-427 cells, and induced differential expression of HIF-1α, AMPK and CS transcripts. A-427 cells increased pAMPK and HIF-1α levels and shifted metabolism increasing OXPHOS; thus supporting cell growth. Conversely, A-549 cells increased HIF-1α protein levels, but did not activate AMPK and diminished OXPHOS. A-549 cells survived by arresting cells in G1-phase. Our findings show that lactic acidosis diminishes Warburg effect in tumor cells, but this change does not necessarily promote a shift to OXPHOS. Hence, lung adenocarcinomas show a differential metabolic response even when they are under the same microenvironmental conditions.